2010
DOI: 10.1007/s00345-010-0635-2
|View full text |Cite
|
Sign up to set email alerts
|

External validation and applicability of the EORTC risk tables for non-muscle-invasive bladder cancer

Abstract: In terms of the applicability of the EORTC risk tables in our patients' population, we conclude that these tables predict accurately the clinical course of patients with NMIBC. Due to the sample size of our study, we can only validate the recurrence model of the EORTC tables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 20 publications
3
34
2
3
Order By: Relevance
“…[9,10] Second-look TUR has gained attention because of the inaccuracy of the pathological diagnosis. [11][12][13] Hernandez et al [14] and Pillai et al [15] conducted different trials to evaluate external validity and applicability of the EORTC risk tables. Due to the sample size of the trial, Hernandez et al [14] could only validate the recurrence model of the EORTC algorithm and Pillai et al [15] were not able to validate the proposed algorithm in their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] Second-look TUR has gained attention because of the inaccuracy of the pathological diagnosis. [11][12][13] Hernandez et al [14] and Pillai et al [15] conducted different trials to evaluate external validity and applicability of the EORTC risk tables. Due to the sample size of the trial, Hernandez et al [14] could only validate the recurrence model of the EORTC algorithm and Pillai et al [15] were not able to validate the proposed algorithm in their patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patient characteristics of other trials were similar to the current study's patient characteristics. [14,15] In contrast to Sylvester's study which had been done in industrialized world, Turkey which is included among the developing countries, has lack of organized health care and a large portion of the patients have significant socioeconomic problems in accessing a convenient health center. As such, increase in the cases with histopathological diagnosis of high grade bladder tumor and concomitant CIS were observed with time.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the EORTC table, several external validation studies were carried out. [4][5][6][7][8][9] Among them, the CUETO group validated the EORTC table using a dataset from the CUETO scoring system. 7 Their results showed that the EORTC tables overestimated the risk of recurrence in all risk groups, as well as the probabilities of progression in higher-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this series, a low number of patients (n = 230) with only primary NMIBC was analyzed, and therefore a full validation could not be done. Hernandez et al recently reported a validation of EORTC tables for recurrence in 417 patients in follow-up with primary TaT1 bladder tumors [7]. Nevertheless, validation of the EORTC risk tables still has not been reported in a large cohort of patients.…”
Section: Introductionmentioning
confidence: 99%